THE IMPACT OF SOCIAL MEDIA IN ISLAMIC STUDIES ON CONSUMER BEHAVIOR TOWARDS SMART WATCHES WITH SPECIAL REFERENCE FOR THE CITY OF ISLAMPUR - Aishwarya Rakate; Hemlata Gaikwad (Universitas Pendidikan Indonesia, 2022)
Smart watches are trendy fashionable and wearable devices which were introduced in India in recent times. The main objective of this study is to understand the impact of social media in Islam on consumer buying behavior. The quantitative survey investigates the factors that influence user behavior towards smartwatches. Data of 160 respondents was collected and analyzed using SPSS and Microsoft Excel software. It has been observed that smart watches are trending in the digital age with the ability to replace smart phones. The findings of this study reveal various influencing factors such as friends, advertisements but most of the respondents are influenced by social factors to buy smart watches. The findings of this study will be useful for marketers and smart watch manufacturing companies to find out consumer perceptions of smart watches, and in Islamic studies this can be a da'wah facility in spreading goodness by optimizing developing technology.